UVA Exposure Combined with Glycation of the Dermis Are Two Catalysts for Skin Aging and Promotes a Favorable Environment to the Appearance of Elastosis - Hervé Pageon; Hélène Zucchi; Sylvie Ricois; Philippe Bastien; Daniel Asselineau (Journal of Aging Research)
Skin aging is the result of superimposed intrinsic (individual) and extrinsic (e.g., UV exposure or nutrition) aging. Previous works have reported a relationship between UV irradiation and glycation in the aging process, leading, for example, to modified radical species production and the appearance of AGEs (advanced glycosylation end products) in increasing quantities, particularly glycoxidation products like pentosidine. In addition, the colocalization of AGEs and elastosis has also been observed. We first investigated the combination of the glycation reaction and UVA effects on a reconstructed skin model to explain their cumulative biological effect. We found that UVA exposure combined with glycation had the ability to intensify the response for specific markers: for example, MMP1 or MMP3 mRNA, proteases involved in extracellular matrix degradation, or proinflammatory cytokine, IL1α, protein expression. Moreover, the association of glycation and UVA irradiation is believed to promote an environment that favors the onset of an elastotic-like phenomenon: mRNA coding for elastin, elastase, and tropoelastin expression is increased. Secondly, because the damaging effects of UV radiation in vivo might be more detrimental in aged skin than in young skin due to increased accumulation of pentosidine and the exacerbation of alterations related to chronological aging, we studied the biological effect of soluble pentosidine in fibroblasts grown in monolayers. We found that pentosidine induced upregulation of CXCL2, IL8, and MMP12 mRNA expression (inflammatory and elastotic markers, respectively). Tropoelastin protein expression (elastin precursor) was also increased. In conclusion, fibroblasts in monolayers cultured with soluble pentosidine and tridimensional in vitro skin constructs exposed to the combination of AGEs and UVA promote an inflammatory state and an alteration of the dermal compartment in relation to an elastosis-like environment.